Regiospecific azidoiodination of alkenes with sodium periodate, potassium iodide, and sodium azide: a high-yield synthesis of beta-iodoazides - Chouthaiwale, Pandurang V.; Karabal, Pratibha U.; Suryavanshi, Gurunath; Sudalai, Arumugam (Synthesis-Stuttgart, 2010)
The combination of sodium periodate, potassium iodide, and sodium azide has been found to be an efficient, simple, and inexpensive reagent system for azidoiodination of alkenes. The regiospecific 1,2-azidoiodination proceeds in an anti-Markovnikov fashion to produce beta-iodoazides in excellent yields.
Keywords: alkenes; azides; azidoiodination; beta-iodoazides; regio-specific

NaIO4-NaN3-mediated diazidation of styrenes, alkenes, benzylic alcohols, and aryl ketones - Kamble, Dayanand A.; Karabal, Pratibha U.; Chouthaiwale, Pandurang V.; Sudalai, Arumugam (Tetrahedron Letters, 2012)
Sodium periodate and sodium azide combination has been found to be an excellent reagent system suitable for the direct diazidation of styrenes, alkenes, benzylic alcohols, and aryl ketones to produce the corresponding vicinal and geminal diazides respectively in high yields under mild reaction conditions. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: alkenes; Aryl ketones; Geminal diazides; Sodium periodate; Vicinal diazides